PWE-221 Improving the practice of nutrition therapy in the critically ill patient. (22nd June 2015) - Jukes, A; Golding, E; Jenkins, J; Morgan, O; Scholey, G
Abstract : Introduction: In 2013, the University Hospital of Wales (UHW) participated in the fourth International Critical Care Nutrition Survey, a period prevalence survey led by Daren Heyland of the Clinical Nutrition Unit, Canada. This Quality Improvement Project aims to compare nutritional practices within and across countries and to highlight strengths and weaknesses leading to practice improvement. Method: Critical Care units were eligible to participate in the survey if they had a minimum of 8 beds, and enrolled a minimum of 20 patients within a set time period. Over 100 patients were screened for enrollment criteria - aged ≥ 18 years of age, mechanically ventilated with 48 h of admission and remained for ≥ 72 h in the unit. For each patient a questionnaire was completed. This included patient demographics, diagnosis, co-morbidities, clinical parameters and severity of illness scores, nutritional status, nutritional requirements, feeding route and when nutrition was commenced. Data was subsequently collected for up to 12 days for actual nutrition received from enteral and parenteral sources in addition to insulin and glycaemic control. Patient outcomes included duration of mechanical ventilation, critical care and hospital outcomes. Data was collected by 2 Dietitians and submitted using the web based data collection tool. UHW data was validated for 3 randomly selected patients, and a comprehensive report comparing our patients and practice with Critical Care units in Europe and overall worldwide was provided by the Clinical Nutrition Unit. Results: 190 Critical Care Units participated in the 2013 International Survey. UHW enrolled 23 of the total 3997 patients and 243 of the 37460 days analysed. The results of UHW–s practice compared with the other units are shown in the Table 1 . Conclusion: UHW was ranked joint 4th in the 2013 International Critical Care Survey and is the highest achievement of any UK hospital to date. The UHW feeding protocol has been further revised as a result of this improvement project and is both evidence based and practical. UHW participated in the 2014 survey and is currently awaiting the results. Disclosure of interest: None Declared.